The Hoysala Emblem - Ishwar Phulari (2021)
A young man slaying a ferocious lion is the emblem you see in every temple built by the Hoysala kings. On either side of the main door to the temple, you will see these sculptures. There are two theories to what it signifies. The first theory is that a lion attacked the Gurukula where a man named Sala was studying. His Guru Sudipta threw a sword at Sala and shouted the words ‘Poy Sala,’ which translates to ‘Strike, Sala.’ Young Sala wrestled the lion, subdued it, and eventually stuck the sword through its belly. When Sala went on to build his own Empire, he named it after his teacher’s words ‘Hoysala.’ Poy has become Hoy here. The second theory is that a later Hoysala ruler, King Vishnuvardhana, created this emblem to signify his victory against a King from the powerful Chola dynasty. The emblem of the Cholas being a lion, this figurine symbolically represents Vishnuvardhana subduing a Chola king. This story is more credible given the inscriptions in the temples. Image credit: Ishwar Phulari